Statistical analysis of home greening efforts in young generation - Toh, Tien Choon; Abudllah, Arham; Goh, Kai Chen; Lew, Yoke Lian; Lee, Chia Kuang; Yong, Felicia Yan-Yan (IOP Publishing Ltd., 2020)
The young generation today inherited an environment that is badly polluted by many human activities. Environmental protection on the other hand is by far not sufficient in view of the fact that it simply could not cope with the pace of damage being done. Apparently leading a green lifestyle is no longer an option but a necessity primarily for the sake of the environment. Sustainability begins at home. The young generation was concerned for the reason that it was burdened with the responsibility to clean up the wastes left by previous generations, and also to restore the environment back to its original or near-original state. Hence, this research aimed to identify the levels of likelihood in home greening efforts in young generation. A questionnaire survey was implemented in Klang Valley, Malaysia to collect quantitative data through closedended questions from 88 young generation males and females residing in that region. Statistical analysis on the usable 85 responses showed that in general, participants were moderately likely to green their homes as the various measures to save the environment achieved reasonable high index values. Underlying structure of home greening efforts revealed 4 underlying dimensions: reduce usage, tap natural sources, adopt energy-efficient technologies, and use green products. This research provided an overview of current home greening efforts in young generation as a tool to promote more specific ways to save the environment while adding further insights to the literature on young generation in this era as consumers and citizens.